ANALYSIS OF ORAL SPEECH EXERCISES IN ENGLISH LANGUAGE LESSONS IN GENERAL SECONDARY SCHOOLS - Hilola Nadirova (Web of Journals Publishing, 2025)
The main goal of this article is to analyze and study the methodological features of the formation of "speaking and listening comprehension skills", which are a component of the activity of oral communication in a foreign language.
Keywords: Communication, speech, listening, skills, analysis.